To vaccinate or not to vaccinate: A mandatory or conscience decision? - Andrew, Daniel (2021)
Faith communities are challenged during the COVID-19 pandemic to urge their members to take a decision to vaccinate or not to vaccinate. The relationship between religion and medical sciences, especially with regard to vaccination, has not always complemented one another, but there is general agreement amongst religions that vaccination is acceptable to save lives. The purpose of vaccination is to secure herd or population immunity, but the spread of misinformation about vaccines and conspiracy theories, some based on religious beliefs, put all vaccination efforts at risk. It ultimately influences the decision people should make to vaccinate or not to vaccinate. The question of mandatory vaccination for all and vaccination based on an individual decision according to conscience seems like a paradox, but the comprehensive second-level normative ethical approach or ethic of responsibility proposed by De Villiers (2020) can be helpful to address this dichotomy. This is in line with ethics in an African context that is indigenous, interdependent and holistic. The paper follows an interdisciplinary approach that incorporates contributions from the fields of medical science, religion and ethics. A comprehensive, second-level, normative ethical approach provides contextual appropriateness and an adequate continuity with ethical traditions that are helpful to address vaccine hesitancy and create therapeutic alliances to address challenges presented by the pandemic.
Keywords: Conscience; ethic of responsibility; Holistic; Indigenous; interdependent; mandatory; Vaccination